2003
DOI: 10.1002/bdd.357
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics and pharmacodynamics of propranolol and atenolol in normolipaemic and hyperlipidaemic obese subjects

Abstract: The lipophilic beta-adrenoreceptor antagonist propranolol and hydrophilic atenolol have been studied to define their pharmacokinetic and pharmacodynamic characteristics in obese patients. A total of 43 subjects were allocated into three study groups: (1) healthy, lean, normolipaemic volunteers, (2) obese normolipaemic subjects, and (3) obese patients with lipid disorders. A crossover method with an interval of 2 weeks was applied for oral 80 mg propranolol and oral 100 mg atenolol administration. Heart rate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…In the study conducted in Poland, the volume of distribution of propranolol was 5±1.2 L/kg, which was within the range of volume of distribution obtained in our study. 33 In another study conducted in Malaysia by Zain-Hamid R and colleagues, volume of distribution following a single 20 mg dose of propranolol was 543.89±292.91 L which was more than the results from our study. 34 Although in our study pharmacokinetic parameters of propranolol were examined as a single dose, but it has shown that the value of distribution with repeated doses decreases due to saturated tissue attachment of the drug.…”
Section: Resultscontrasting
confidence: 68%
“…In the study conducted in Poland, the volume of distribution of propranolol was 5±1.2 L/kg, which was within the range of volume of distribution obtained in our study. 33 In another study conducted in Malaysia by Zain-Hamid R and colleagues, volume of distribution following a single 20 mg dose of propranolol was 543.89±292.91 L which was more than the results from our study. 34 Although in our study pharmacokinetic parameters of propranolol were examined as a single dose, but it has shown that the value of distribution with repeated doses decreases due to saturated tissue attachment of the drug.…”
Section: Resultscontrasting
confidence: 68%
“…In an in vivo study directly measuring renal hemodynamics, obese patients had a greater renal vasodilatory response to short term angiotensin converting enzyme inhibition with captopril than normal-weight individuals [51]. Although there are no measurable changes in pharmacokinetic handling of beta blockers in obesity [52], another study demonstrated that obese patients had significantly greater blood pressure response compared to lean patients after treatment with combined alpha- and beta-adrenergic blockade [53]. We recently performed an observational study evaluating the renal effects of time-updated exposure to renin-angiotensin system blockade compared to any other antihypertensive therapy in over 200,000 obese, non-diabetic, hypertensive patients in the United Kingdom.…”
Section: Challenges In the Pharmacologic Management Of Hypertension Imentioning
confidence: 99%
“…For lipophilic agents, clearance can be unchanged/decreased (propranolol 23,24,39,40,42 ) or increased (metoprolol, 43 nebivolol 41 ). Because these drugs are primarily hepatically cleared this finding potentially reflects alterations in metabolic reactions and enzymes.…”
Section: Methodsmentioning
confidence: 99%